The Effect of Swimming Style Training on Personality and Swimming Ability in Beginners in Rejang Lebong - Bengkulu - Fitriana Belajaya Negara; Hermawan Pamot Raharjo; Sri Sumartiningsih; Agung Wahyudi (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2023)
The background to this research is that the training program for beginner swimmers is still ineffective and the personality and abilities of beginner swimmers in Rejang Lebong are still unknown. The aim of this research was to determine the interaction of breaststroke and freestyle swimming training on the swimming ability, speed, personality and style mastery of beginner swimmers in Rejang Lebong. This type of research used by quasi-experiment, the sample population is 40 people, the sampling technique in this research used by purposive sampling, namely with certain considerations, the data collection technique used by observation, a swimming ability test, namely a speed of 25 meters, filling out a questionnaire, and documentation. The data analysis technique used by normality, percentage and homogeneity tests with normality results of 0.200 > 0.05 with a normal distribution, a percentage of 87.50% with a very good category, and homogeneity test results of 0.000 < 0.05, namely there is a significant difference between results of swimming 25 meters breaststroke and swimming 25 meters freestyle in pretest and posttest. The conclusion of this research is that there is an interaction between the training methods of the breaststroke group and the freestyle group on the swimmer's personality and ability.